A SHIFTIN TRADITIONAL WISDOM OF SEMENDE TRIBE IN PULAU PANGGUNG TANGGAMUS - Mulyaningsih, Handi; Kartika, Tina; Hertanto, Hertanto; Darmastuti, Ari (Sosiohumaniora, 2021)
The traditional wisdom of tunggu tubang has shifted  due to economic needs, lack of agricultural land, job mobility, marriage with other than Semende tribe, which impacts the rights fulfilling and obligations of tunggu tubang. However, this shift has been  responded to by innovations so that this traditional wisdom persisted. This research  is to describe innovations in maintaining the traditional wisdom. This research uses descriptive quantitative method with 40 randomly chosen respondents. Data were taken from interviews using a questionnaire, and  interviews with key informants. The data were analyzed quantitatively with frequency tables, given the meaning with the structural functional approach of Talcott Parson, that traditional wisdom still functions when able to adapt,  goal attainment, integration, latent maintenance. The results showed:  92.5% tunggu tubang to get rights to houses, gardens, fields and carrying out their obligations, but 7.5% without these rights (tepang bangkang) so they cannot carry out their obligations, namely occupying an inheritance house, taking care of their parents and their younger siblings. Tunggu tubang property sold out.This violation is tolerated because of economic necessity. But tepang bangkang still the decision maker in the family and  can give the right for the next tunggu tubang. If tunggu tubang married to someone other than Semende tribe, her husband follows it.If working outside the city, rights are still given while obligations are carried out indirectly. This adaptation makes the  traditional wisdom survive, be the goal of life, carries out the function of integration, but the function of pattern maintenance is getting weaker.